Dampak Positif Fraksi Etil Asetat dari Kalanchoe pinnata terhadap Antibodi Anti-Smith dan Sel T Reg pada Mencit Lupus - NIKEN INDRIYANTI; JUNAIDI KHOTIB; JOEWONO SOEROSO (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Kalanchoe pinnata (Lmk) Pers is a medicinal plant that has many activities, such as antioxidant, anti-infl ammation and immunosuppressant activities. Based on our previous study, aqueous extract of this plant leaves has a repairing eff ect on lupus nephritis model. The expected active compounds are flavonoids. Those compounds are separated in the ethyl acetate fraction. Therefore, this study observed the activity of the ethyl acetate fraction of Kalanchoe pinnata (Lmk) Pers on reducing the level of Anti- Smith autoantibody and the regulation function of CD4+CD25+ T reg in lupus mice. The experimental groups were a negative control group that received placebo, ethyl acetate fraction of Kalanchoe pinnata (Lmk) Pers (EF-KP) group and a positive control group that received cyclophosphamide. The anti-Sm level was measured by using indirect ELISA. The spleen cells were prepared for CD4+CD25+ T reg assay using fl ow cytometry. The result of this experiment was a reduction of anti-Sm antibody level. The decrease was suffi cient to stabilize lupus condition. The fl ow cytometry assay results showed the increase in the relative percentage of CD4+CD25+ T reg. This function can inhibit the reactivity of autoantigens, so it prevents tissue and organ damage from lupus. However, further research is needed to observe the complete mechanism.